2014
DOI: 10.1007/s00034-014-9851-0
|View full text |Cite
|
Sign up to set email alerts
|

Fast Mode Decision for Multiview Video Coding Based on Just Noticeable Distortion Profile

Abstract: Multiview video coding (MVC) achieves an excellent coding gain using exhaustive variable size mode decision in intra-view prediction and inter-view prediction. However, the high computational complexity prevents it from real-time application. In this paper, a fast intra-view mode decision and inter-view prediction termination algorithm based on just noticeable distortion (JND) is proposed to speed up the search process of motion estimation (ME) and disparity estimation (DE). The basic idea of the method is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Traditional JND researches have shown that, due to the masking effect of the image [10][11][12], bitrate can be reduced without causing a subjective quality degradation when working within the JND range. This means that even if the asymmetric stereoscopic masking effect is not taken into account, as long as a larger QP is used to symmetrically encode the image in a certain range of JND, human eyes are still unable to observe the subjective quality changes of degraded reconstructed images.…”
Section: Comparison and Analysis Of Qp Threshold For Symmetric And Asmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional JND researches have shown that, due to the masking effect of the image [10][11][12], bitrate can be reduced without causing a subjective quality degradation when working within the JND range. This means that even if the asymmetric stereoscopic masking effect is not taken into account, as long as a larger QP is used to symmetrically encode the image in a certain range of JND, human eyes are still unable to observe the subjective quality changes of degraded reconstructed images.…”
Section: Comparison and Analysis Of Qp Threshold For Symmetric And Asmentioning
confidence: 99%
“…On the other hand, traditional two-dimensional (2D) image/video just noticeable distortion (JND) researches have shown masking effects of texture [10] and luminance [11] for human perception. Such researches have succeeded in characterizing effects of these factors on perceived thresholds using explicit JND models [12].…”
Section: Introductionmentioning
confidence: 99%
“…In detail, JND models can be estimated in pixel domain or transform domain. In pixel domain, a JND model is often derived by investigating the luminance adaption (LA) and spatial contrast masking (CM) [24]. The JND models in transform domain usually utilize human vision sensitivities of different frequency components, and the contrast sensitivity function (CSF) is frequently applied in identifying the base thresholds [25].…”
Section: Introductionmentioning
confidence: 99%